PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, KONTRAK UTANG, TINGKAT KESULITAN KEUANGAN PERUSAHAAN, PELUANG PERTUMBUHAN, RISIKO LITIGASI DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI (Survey Pada Perusahaan Manufaktur yang Terdaftar di BEI) - Raja Erwin Saputra; Kamaliah '; Hariadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This reserch aims to examine the effect of managerial ownership structure, debt covenant, financial distress, growth opportunities, risk of litigation and leverage which accounting conservatism. This study uses secondary data. Sample selection technique used is purposive sampling. 53 companies listed in Indonesia stock exchange from 2010 to 2012. The analytical method is miltiple linear regression using SPSS version 20. Data collection for this research is documentation. The influenced managerial ownership structure variable for the accounting conservatism were 0.028, debt covenant for the accounting conservatism were 0.009, growth opportunities for the accounting conservatism were 0.029, risk of litigation were 0.001, and leverage were 0.045 have a significant influence on accounting conservatism. Meanwhile financial distress for the accounting conservatism were 0.667, the result show that financial distress wasn’t significant effect. The big influence of managerial ownership structure, debt covenant, growth opportunities, risk of litigation and leverage were 61.20%.Keywords : Managerial Ownership Structure, Debt Covenant, Growth Opportunities, Risk of Litigation and Leverage